Community structure detection algorithm based on link prediction. (12th October 2021) - Dai, Gang; Wang, Quanxin; Xu, Baomin; Sun, Lijun
Community structure identification has received a great effort among computer scientists who are focusing on the properties of complex networks. The label propagation algorithm is a near linear time algorithm to find a good community structure. Despite various subsequent advances, an important issue of this algorithm is the efficiency and accuracy of the identified community structure. In this paper, we propose a novel community detection algorithm by using link prediction algorithm based on label propagation. The method is the first to introduce the idea of link prediction into community detection. The experimental results show that the proposed method is less resolution limited than modularity optimising methods, and it can be more effective in detecting communities.